The Influence of The Career Development System on Employee Performance Is Mediated by Job Promotions at BPJS Ketenagakerjaan Branch Offices Throughout Medan Raya - Harri Kahfi; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
In this study, researchers wanted to see the direct and indirect effects between the independent variable career development system variables and job promotion as a moderating variable and employee performance as the dependent variable. This type of research uses quantitative, this research was conducted at BPJS ketenagakerjaan Branch Office Se-Medan Raya. The population of this study were 132 employees and the sample used was the entire population using the saturated sample technique. The data source used is primary data source and data collection is done by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows The Career Development System has a positive and insignificant effect on employee performance with an original sample value of 0.037 and P values of 0.706. Career Development System has a positive and significant effect on job promotion with an original sample value of 0.436 and p values of 0.000. Job promotion has a positive and significant effect on employee performance with an original sample value of 0.729 and p values of 0.000. Career Development System has a positive and significant effect on employee performance through indirect job promotion with original sample results of 0.318 and p values of 0.000.